Comparisons of Health Expenditure in the Pacific Island Countries using National Health Accounts - Hopkins, Sandra; Irava, W.; Tin, K. (Massey University and Fiji School of Medicine, 2010)
National Health Accounts (NHA) is an important monitoring tool for health policy and health systems strengthening. A pilot project amongst three Pacific Island Countries {PICs) to assist in developing their NHAs, allowed these countries to identify their sources of health funds, the health providers on which these funds are spent, and the types of health goods and services provided. In this paper we report same of the findings from the NHA exercises in FSM, Fiji and Vanuatu. The development of these NHA country re parts have allowed these countries to better understand the flow of financial resources from financing agents, to health providers, and to health functions. The NHA findings across the three countries enabled a comparative analysis of health expenditures between the three countries as well as with countries in the Asia Pacific Region.